2015
DOI: 10.1136/bjophthalmol-2015-307111
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing big-bubble formation during deep anterior lamellar keratoplasty in keratoconus

Abstract: The rate of successful big-bubble formation was 79.2% in keratoconus. Among the different factors, recipient sex and trephination size significantly influenced this rate. Females had a lower probability of big-bubble formation, and a large trephination size was associated with an increase in the probability of achieving a bare DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…A large trephination size has been reported to be associated with an increase in the probability of successful big bubble formation in keratoconus eyes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large trephination size has been reported to be associated with an increase in the probability of successful big bubble formation in keratoconus eyes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…DALK with DM perforation is considered a surgical challenge with a reported incidence of 4.4%–39%. 1 5 16 17 18 Despite the widespread use of DALK, the management of such perforation remains a contentious topic, and there is variation in current practice toward the conversion to PKP. Since 2014, we started the implementation of a new concept, completing DALK surgery regardless of the size or the site of DM tears.…”
Section: Discussionmentioning
confidence: 99%
“…Although they did not clearly specify the types of BBs, Feiz et al . 25 , reported that male patients and large trephination sizes increased the rate at which detached bare DM was achieved in DALK. Furthermore, in prior reports of ex vivo studies of the BB technique, the rate of Type II BB formation was relatively low, ranging from 6.3% to 23.8% 12,16,26 .…”
Section: Discussionmentioning
confidence: 99%